Nana. Vol. 1 - Yazawa, Ai, 1967- (Shojo beat manga., 2025)
"A chance meeting on a train to Tokyo sends two girls named Nana on a collision course with destiny! After a string of epic romantic failures, Nana Komatsu is ready to take control of her life and get a clean start in the big city. After prioritizing her musical ambitions over love, Nana Osaki is ready to stomp her way to the top of Tokyo's punk scene. With determination in their hearts and dreams in their eyes, these two women are ready to take the world by storm! Butfirst, they need a place to live. Roommates, anyone? Anxious to getinto a Tokyo groove, both women are on the prowl for a funky and cheap place to live.But inexpensive apartments in Japan's capital cityare hard to find. Thank goodness each Nana has a clique of cool friends willing to help out. Too bad these friends are a little eccentric!"--